Hair Growth Promoting Effect of Urticadioica L - Myagmar, Khaliun; Lkhagvasuren, Enkhsaikhan; Semchin, Munkhbayar (Central Asian Journal of Medical Sciences, 2018)
Objectives: We investigated the effect of Urticadioica L extracts on hair growth by using in-vitro and ex vivo study methods. Methods: Human single hair follicle and dermal papilla cells obtained from scalp skin samples of healthy volunteers. We evaluated the effect of Urticadioica L on hDPCs and on ex vivo hair follicle organ culture. Hair follicle matrix cell’s proliferation marker Ki-67 identified by immunoflurescence staining. Results: Urticadioica L ethanol extracts promoted elongation of the hair shaft and reduced catagen transition of human hair follicles in organ culture model. E.extract of Urticadioica L increased Ki-67 positive matrix keratinocytes. Conclusions: Urticadioica L ethanol extract enhanced human hair growth in ex vivo organ culture model. Future study is needed related to its mechanism of hair growth.